Diagnostic Classification of Bruch's Membrane Opening-Minimum Rim Width and Retinal Nerve Fiber Layer Thickness in Myopic Eyes by Optical Coherence Tomography - Wang, Geng; Zhen, Miaoru; Liu, Shasha; Qiu, Kunliang; Liu, Cui; Wang, Ji; Zhang, Mingzhi (Frontiers in Medicine, 2021)
Purpose:To compare the diagnostic classification of Bruch’s membrane opening-minimum rim width (BMO-MRW) and RNFL thickness in normal myopic subjects by using Optical Coherence Tomography (OCT). Methods: This cross-sectional study involved 75 healthy myopic subjects (spherical equivalent (SE) ≤-0.5D) from April 2019 to January 2020. One eye of each subject was randomly selected for examination.BMO-MRW and peripapillary RNFL thickness were measured by Spectral-domain OCT (Spectralis, Heidelberg Engineering GmbH, Heidelberg, Germany). All the subjects were divided into 3 groups: low myopic group (SE>-3D), moderate myopic group(-6D